Ligand Engineering in Tin-Based Perovskite Solar Cells - Li, Peizhou; Cao, Xiangrong; Li, Jingrui; Jiao, Bo; Hou, Xun; Hao, Feng; Ning, Zhijun; Bian, Zuqiang; Xi, Jun; Ding, Liming; Wu, Zhaoxin; Dong, Hua (Nano-Micro Letters, 2023)
Perovskite solar cells (PSCs) have attracted aggressive attention in the photovoltaic field in light of the rapid increasing power conversion efficiency. However, their large-scale application and commercialization are limited by the toxicity issue of lead (Pb). Among all the lead-free perovskites, tin (Sn)-based perovskites have shown potential due to their low toxicity, ideal bandgap structure, high carrier mobility, and long hot carrier lifetime. Great progress of Sn-based PSCs has been realized in recent years, and the certified efficiency has now reached over 14%. Nevertheless, this record still falls far behind the theoretical calculations. This is likely due to the uncontrolled nucleation states and pronounced Sn (IV) vacancies. With insights into the methodologies resolving both issues, ligand engineering-assisted perovskite film fabrication dictates the state-of-the-art Sn-based PSCs. Herein, we summarize the role of ligand engineering during each state of film fabrication, ranging from the starting precursors to the ending fabricated bulks. The incorporation of ligands to suppress Sn2+ oxidation, passivate bulk defects, optimize crystal orientation, and improve stability is discussed, respectively. Finally, the remained challenges and perspectives toward advancing the performance of Sn-based PSCs are presented. We expect this review can draw a clear roadmap to facilitate Sn-based PSCs via ligand engineering. Highlights: 1 Systematic summary of ligand engineering in Sn-based perovskite solar cells at the molecular level (oxidation-suppression), crystal structural level (bulk-defect passivation and crystal orientation optimization), and film level (film stability). 2 The classification and composition of ligand engineering in the review are the same as the actual preparation process, which will help researchers to understand the role of ligands in combination with the actual experiment process. 3 Description of ligands focuses on the function of each functional group; the relevant conclusion can be universal.